Proposed new design for Playstation Centre at Lot 48-54, 5th Floor, Berjaya Times Square, No 1, Jalan Imbi, 55100 Kuala Lumpur / Mohd Firdaus Che Abu Bakar - Che Abu Bakar, Mohd Firdaus (Faculty of Architecture, Planning and Surveying, 2008)
The main objective of this project is to propose a new design for Playstation Centre and to develop a design scheme that would show the true colors and the variety of Sony Playstation’s sleek design and to apply it in the interior of this project. It is a challenge to design a centre and at the same time functional as a retail and to attract customers that will be the cliche to most of the retail that will necessarily focusing on the design and the display systems itself. This project offers a comprehensive range of facilities and spaces according to the guidelines set up by the client. A series of interviews and observation has been conducted in order to collect relevant data and information. Based on the case study and observation, it can be concluded that it is vital to create and design a centre or retail spaces that will fulfill the client and at the same time customer’s needs and also adapting the appropriate design concept and schemes in order to enhanced the success of the brand itself. Besides that, t is also essential for one centre or retail to have the space that is compelling and also inviting for the main point is to see the brand itself and also the main objective for retail is to sell and giving information to public about the brand. Choosing the right site is also very important to ensure the target market is always at hand and also that is near to the public. Other than that, choosing a suitable design image and also concept is always important to as it determines the schemes of the interior are. The proposed design concept and image needs to be able to be highly blended together for it to work with flying colors. Last but not least, hopefully Sony Playstation will be always in the hearts of every gamers as it offers a variety range of games console and also highly satisfying line story games.